Application of laser light scattering to the determination of molecular weight, second virial coefficient, and radius of gyration of chitosan. (5th December 2018) - Shaheen, Mohamed E.; Ghazy, Ahmed R.; Kenawy, El-Refaie; El-Mekawy, Farouk
Abstract: The static laser light scattering technique was applied to determine the molecular weight, second virial coefficient, and radius of gyration of chitosan in aqueous solutions at room temperature. The angular distribution of the intensity of light scattered from chitosan solutions at different concentrations was exploited to calculate the weight-average molecular weight, second virial coefficient, and the radius of gyration by applying the Zimm plot method. The refractive index of the solvent and refractive index increment required for the determination of these parameters were determined experimentally using a home-built Mach-Zehnder interferometer. A continuous wave He-Ne laser operating at a wavelength of 543 nm and at a power of 2 mW was used as a light source for both light scattering and Mach-Zehnder interferometer experiments. The calculated values of the refractive index increment, the weight-average molecular weight, the second virial coefficient and the radius of gyration were found to be 0.2378 mL/g, 7.96 × 10 5  g/mol, 3.1 × 10 −5  mol mL/g 2, and 207 nm, respectively.